2021
DOI: 10.1021/acscatal.1c03331
|View full text |Cite
|
Sign up to set email alerts
|

The Confined Interlayer Growth of Ultrathin Two-Dimensional Fe3O4 Nanosheets with Enriched Oxygen Vacancies for Peroxymonosulfate Activation

Abstract: Developing iron-based catalysts with superior activity and stability is a longterm goal for peroxymonosulfate (PMS) activation in advanced oxidation processes. Combining the confined interlayer growth strategy with melt infiltration under dry-chemical conditions, we successfully synthesized ultrathin 2D Fe 3 O 4 nanosheets with a monolayer thickness of about 1 nm. Atomic force microscopy, CS-corrected high-resolution transmission electron microscopy, X-ray photoelectron spectroscopy, X-ray absorption fine stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(36 citation statements)
references
References 70 publications
(122 reference statements)
0
35
0
Order By: Relevance
“…Most of the reported studies found acetonitrile, MeCN, to be one of the suitable solvents for this cascade oxidative dearomatization of indoles. , Different oxidants such as molecular oxygen (O 2 ), H 2 O 2 , TBHP, and peroxymonosulfate were used for this type of oxidative dearomatization reaction. ,, For the current study, peroxymonosulfate as oxidant was preferred as H 2 O 2 hampers Fe chemistry, leading to tar formation. , Similarly, catalytic reactions mediated by a Fe-catalyst with O 2 and TBHP as oxidants are reported to have slow reaction kinetics . Recent studies showed that the peroxymonosulfate can be a suitable oxidant for the Fe-based catalytic oxidation reaction. , For further confirmation, reactions were performed with all the oxidants using 0.01 g of Fe 2 O 3 -Y, 3 mmol indole, and 1 mmol individual oxidants. No C2-trimerized product was obtained under this reaction conditions with H 2 O 2 , O 2 , and TBHP.…”
Section: Catalytic Studymentioning
confidence: 94%
See 1 more Smart Citation
“…Most of the reported studies found acetonitrile, MeCN, to be one of the suitable solvents for this cascade oxidative dearomatization of indoles. , Different oxidants such as molecular oxygen (O 2 ), H 2 O 2 , TBHP, and peroxymonosulfate were used for this type of oxidative dearomatization reaction. ,, For the current study, peroxymonosulfate as oxidant was preferred as H 2 O 2 hampers Fe chemistry, leading to tar formation. , Similarly, catalytic reactions mediated by a Fe-catalyst with O 2 and TBHP as oxidants are reported to have slow reaction kinetics . Recent studies showed that the peroxymonosulfate can be a suitable oxidant for the Fe-based catalytic oxidation reaction. , For further confirmation, reactions were performed with all the oxidants using 0.01 g of Fe 2 O 3 -Y, 3 mmol indole, and 1 mmol individual oxidants. No C2-trimerized product was obtained under this reaction conditions with H 2 O 2 , O 2 , and TBHP.…”
Section: Catalytic Studymentioning
confidence: 94%
“…56 Recent studies showed that the peroxymonosulfate can be a suitable oxidant for the Fe-based catalytic oxidation reaction. 57,58 For further confirmation, reactions were performed with all the oxidants using 0.01 g of Fe 2 O 3 -Y, 3 mmol indole, and 1 mmol individual oxidants. No C2-trimerized product was obtained under this reaction conditions with H 2 O 2 , O 2 , and TBHP.…”
Section: Catalytic Studymentioning
confidence: 99%
“…2(c)). 34,39 It is noted that even with different Ce : Bi ratios, the binding energy of Ce and Nb display barely any change (Fig. S11a-c, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…75,76 For instance, Wang et al revealed that the Fe-O coordination number (3.4) in 2D Fe 3 O 4 containing ample oxygen vacancies was lower than that in commercial Fe 3 O 4 (4.6). 77 This will correspondingly affect Fenton-like catalytic performance since the coordination number of surface Fe sites is closely related to the H 2 O 2 adsorption and activation process. 30,51 Except for oxygen vacancies, the promoting effects of some other anion vacancies (i.e., sulfur vacancies in Fe sulde) on Fenton-like processes have also been reported with a similar mechanism to oxygen vacancies.…”
Section: Defectsmentioning
confidence: 99%